On the road to a unified market for energy efficiency: the contribution of white certificates schemes - Louis-Gaëtan Giraudet; Dominique Finon (Fondazione Eni Enrico Mattei (FEEM), 2010)
White certificates schemes mandate competing energy companies to promote energy efficiency with flexibility mechanisms, including the trading of energy savings. So far, stylized facts are lacking and outcomes are mainly country-specific. By comparing results of British, Italian and French experiences, we attempt to identify the core determinants of their performances. We show that (i) white certificates schemes are depicted in theoretical works as mandatory subsidies on energy efficiency goods recovered by an end-use energy tax, whereby white certificates exchanges are not a central feature; (ii) at current stages, existing schemes are cost-effective and economically efficient, with large discrepancies though; (iii) the hybrid subsidy-tax mechanism seems valid but conditional to cost pass through permissions; otherwise, obliged energy companies merely promote information on the 'downstream' side (i.e. at the consumer level); (iv) although white certificates exchange between different types of actors involved can be important as in Italy, trade among obliged companies is negligible; instead, flexibility sustains vertical relationships between obliged parties and 'upstream' partners (i.e. installers, energy service companies). In this respect, we support the view that white certificates schemes are a policy instrument of multi-functional nature (subsidisation, information, technology diffusion), whose static and dynamic efficiency depends upon the consistency between a proper definition of long-term energy savings, the appropriate cost-recovery permission and a fine coordination with other instruments. We finally propose a four stages deployment pattern, along which fragmented markets for energy efficient technologies get closer to create a unified market delivering energy efficiency as a homogeneous good.
Keywords: Q4; 330; White Certificates Schemes; Static Efficiency; Dynamic Efficiency; Vertical Organisation; Policy Coordination